2013
DOI: 10.1097/meg.0b013e32835f0786
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic liver disease/nonalcoholic fatty liver disease index

Abstract: The ANI scoring system may be used for the estimation of alcoholic origin of steatosis/steatohepatitis and may help in triaging patients for liver biopsy. ANI less than -0.66 indicates NAFLD, whereas ANI greater than -0.66 confirms the alcoholic etiology, but does not exclude the contribution of associated factors toward the development of fatty liver in a Serbian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Meanwhile, Dunn et al more recently reported the alcoholic liver disease (ALD)/non-alcoholic fatty liver disease (NAFLD) index (ANI) for the differentiation of ALD and NAFLD [ 11 ]. ANI is a formula derived from four independent ALD predictors: MCV, the AST/ALT ratio, body mass index (BMI), and male sex that has been reported as capable of distinguishing ALD from NAFLD [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Dunn et al more recently reported the alcoholic liver disease (ALD)/non-alcoholic fatty liver disease (NAFLD) index (ANI) for the differentiation of ALD and NAFLD [ 11 ]. ANI is a formula derived from four independent ALD predictors: MCV, the AST/ALT ratio, body mass index (BMI), and male sex that has been reported as capable of distinguishing ALD from NAFLD [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 Alcoholic liver disease (ALD), induced by excessive alcohol consumption, and nonalcoholic fatty liver disease (NAFLD), caused by obesity and insulin resistance, are the most common diseases associated with hepatic steatosis, although hepatic steatosis is also found in patients with hepatitis C virus infection and those receiving certain medications, such as corticosteroids and amiodarone. 4 , 5 Regardless of etiology, hepatic steatosis can progress to end stage liver disease such as liver cirrhosis or hepatocellular carcinoma. 1 , 6 8 Moreover, NAFLD has emerged as one of the risk factors for coronary artery disease and type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty liver disease is very common in certain population groups such as alcohol consumers (45%), dyslipidemic patients (50%), those who are obese (75%) and more than 95% in those who are obese alcohol consumers. [5] The standard of diagnosis in fatty liver disease is liver biopsy and histopathology. Currently specialized cross sectional imaging has become helpful in diagnosis of fatty liver albeit the need for liver biopsy.…”
Section: Discussionmentioning
confidence: 99%